Animal cloning and genome editing in buffalo, with special reference to India - Naresh Selokar; Manoj Kumar Singh (Revista Científica)
India owns the best buffalo breeds, particularly Murrah, which is famous worldwide for high milk production. India’s white and pink revolution cannot be imagined without the contribution of buffalo, and to achieve this, the best productive animals need to be produced through scientific interventions. Animal cloning is a technique used to produce multiple copies of the best animals without normal reproduction. In India, buffalo cloning has already happened, and India’s first cloned buffalo was produced in 2009. Later, several buffalo clones were produced, and attempts are ongoing to produce a stock of more elite animals. Buffalo cloning has made its way from scientific manuscripts to farmers’ farms. Recently, genome editing has emerged as a powerful tool to manipulate the genomes of several animal species. Various livestock models have already been produced, and it can be foreseen that more model animals will be produced in the future using the CRISPR-Cas system. These success stories have opened multiple prospects for Indian researchers. In this article, we provide an overview of the progress of buffalo cloning in India and new initiatives on genome editing.